2008
DOI: 10.1007/s00442-008-1162-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire frequency on oak litter decomposition and nitrogen dynamics

Abstract: Fire can alter a multitude of ecosystem properties that have the potential to affect rates of litter decomposition and nitrogen dynamics. In this study, we examined the effect of long-term variation in fire frequency in Minnesota oak savanna on rates of litter mass loss of a common tree species (Quercus ellipsoidalis) to determine how site and intraspecific litter characteristics impacted by variation in fire frequency affect rates of decomposition, litter N dynamics, and litter microbial biomass. Although an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…Compared to decomposition rates of leaf litter of congeners in natural forests and prairies at the Cedar Creek Long Term Ecological Research site (35 km north of the study site) (Hobbie 2008;Hernández and Hobbie 2008;McBrayer and Cromack 1980), decomposition rates were about twice as fast in the gutter. Rapid decomposition in the gutter may have resulted from several factors.…”
Section: Litter Decompositionmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared to decomposition rates of leaf litter of congeners in natural forests and prairies at the Cedar Creek Long Term Ecological Research site (35 km north of the study site) (Hobbie 2008;Hernández and Hobbie 2008;McBrayer and Cromack 1980), decomposition rates were about twice as fast in the gutter. Rapid decomposition in the gutter may have resulted from several factors.…”
Section: Litter Decompositionmentioning
confidence: 85%
“…Indeed, litter collected from in this experiment was more fragmented than that collected in experiments we have conducted in nearby forests and grasslands (personal observation). Regardless of the cause, decomposition rates were high, such that only about 20-40 % of the initial mass was remaining after 1 year, compared to 50-85 % in natural forests and savanna in the region (Hobbie 2008;Hernández and Hobbie 2008;McBrayer and Cromack 1980). Decomposition exhibited unique dynamics in the street, as well, exhibiting a period of very rapid initial mass loss (of up to 22 %) for the first 1.5 months of decomposition.…”
Section: Litter Decompositionmentioning
confidence: 99%
“…Similarly, previous studies have reported soil organic matter to increase, decrease or have no detectable change depending on the frequency of fire (Johnson, 1992;Phillips et al, 2000;Neill et al, 2007). Although N is one of the elements most likely to show large decreases with a high temperature fire due to volatilization, a significant part of the site N may become more available to plants after a fire (Bell and Binkley, 1989;Hernandez and Hobbie, 2008). In fact, many mineral elements become more available in the ash left by fire and are subject to leaching or uptake by new plant growth (Wells et al, 1979;DeBano et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…In Eucalyptus forest, Brennan and others (2009) attributed slower rates of decomposition to negative effects of frequent fire on invertebrate decomposer abundance, while in seasonal Amazonian forest repeated burning was thought to have slowed decomposition rates through altered micro-climatic conditions (particularly by increasing temperature and decreasing relative humidity, resulting in a drier environment) (Silveira and others 2009). Other potential mechanisms include interactions with herbivory (Kay and others 2008), and long-term alterations of litter quality by fire (Hernández and Hobbie 2008).…”
Section: Ayres and Others 2009mentioning
confidence: 99%